2019
DOI: 10.9782/16-00049
|View full text |Cite
|
Sign up to set email alerts
|

Convergent and Concurrent Validity of the Lithuanian Version of the Behavioral and Emotional Rating Scale-2 Teacher Rating Scale

Abstract: Given the increasing international calls for more strength-based assessment, there is a need for European schools, mental health programs and family service agencies to identify psychometrically sound instruments in their native languages. The purpose of this study was to examine the convergent and concurrent validity for [?] the Behavioral and Emotional Rating Scale-2 Teacher Rating Scale (BERS-2; Epstein, 2004) as translated into Lithuanian by comparing it with the Strengths and Difficulties Questionnaire (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…They found that some of the observation instrument scores were psychometrically sound (i.e., favorable interrater reliability), but they caution their continued use because the scales may no longer be aligned to current conceptions of giftedness. Additionally, several other studies have also illustrated adequate validity and reliability of teacher ratings using different types of observation scales (see Hunter et al, 2018;Kettler & Albers, 2013;Lopata et al, 2020;Nordness et al, 2019;Reid et al, 2014;Smith et al, 2018). Further, to identify students for gifted services and to ensure the scores on the measures are reflective of studentobserved behaviors, teachers need to be provided adequate and appropriate training to use the scales (Renzulli et al, 2013;S ¸ahin & Çetinkaya, 2015;Styck et al, 2021;Szymanski & Shaff, 2013).…”
Section: Variability In Teacher Ratings Of Student Abilitiesmentioning
confidence: 99%
“…They found that some of the observation instrument scores were psychometrically sound (i.e., favorable interrater reliability), but they caution their continued use because the scales may no longer be aligned to current conceptions of giftedness. Additionally, several other studies have also illustrated adequate validity and reliability of teacher ratings using different types of observation scales (see Hunter et al, 2018;Kettler & Albers, 2013;Lopata et al, 2020;Nordness et al, 2019;Reid et al, 2014;Smith et al, 2018). Further, to identify students for gifted services and to ensure the scores on the measures are reflective of studentobserved behaviors, teachers need to be provided adequate and appropriate training to use the scales (Renzulli et al, 2013;S ¸ahin & Çetinkaya, 2015;Styck et al, 2021;Szymanski & Shaff, 2013).…”
Section: Variability In Teacher Ratings Of Student Abilitiesmentioning
confidence: 99%